Analisis Keamanan Website SIASAT Menggunakan Teknik Footprinting dan Vulnerability Scanning - Kendek Allo, Alvin; Widiasari, Indrastanti Ratna (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Universitas Kristen Satya Wacana (UKSW) is one of the private universities in Indonesia that actively utilizes internet technology and its Website to support academic and non-academic activities. SIASAT (Satya Wacana Academic Information System) provides important information confidentially to the community or makes this information only accessible to users who have an account. Regarding security, SIASAT has experienced problems, and threats such as SQL Injection, brute force, and so on which still happen frequently. Problems related to the security and confidentiality of data in computer networks are Privacy (confidentiality) data must be kept away from unauthorized parties. Integrity (integrity) ensures that the information sent remains intact or without changes. Authenticity (authenticity) is a procedure for knowing that a user is truly authorized to access a system. Authenticity could be password, PIN, fingerprints, or other identification. Non-repudiation (irrefutable proof) is proof to ensure that the user has full access to the services used in a system. A system can be categorized as unsafe if the above issues cannot be met. Therefore, by using Footprinting and vulnerability scanning techniques, analysis can be carried out on the SIASAT Website to overcome this problem. This research was carried out using an approach of ethical Hacking, with an emphasis on level Footprinting and vulnerability scanning. The results of this research have found information related to the SIASAT Website and several vulnerability warnings after scanning with high to low-risk levels.